DEFINITION OF AN INTERVENTION POLICY FOR ROAD MAINTENANCE AND CONSERVATION: COST-BENEFIT ANALYSIS IN BENGUELA, ANGOLA - Raimundo, Cláudio Cipriano; Kai, José Paulo (Editora Impacto Científico, 2025)
Considering the accelerated degradation of road infrastructure in Angola and its socioeconomic impacts, this study aims to propose an efficient intervention policy for road maintenance and conservation, focusing on cost-benefit analysis. To this end, a mixed-methods investigation was conducted, combining qualitative (semi-structured interviews) and quantitative (surveys and technical inspections) methods in the municipality of Benguela. In this way, it is observed that the absence of formal conservation plans, insufficient funding, and the predominance of a reactive management model are the main obstacles. Recurring pathologies in flexible pavements are identified, such as cracks, alligator cracking, and deformations. Four types of intervention are proposed, ranging from localized actions to complete redesign, which allows us to conclude that the adoption of preventive policies, based on cost-benefit analyses and supported by emerging technologies, is essential to ensure the sustainability of the road network and optimize public resources.DOI: https://doi.org/10.56238/edimpacto2025.086-003